The Impact of Energy Production, Consumption and Import on the Budgetary Energy Requirement of Indonesia - Haryono, Bambang Santoso; Hakim, Abdul; Mardiono, Mardiono; Safri, Safri; Sholihah, Qomariyatus (International Journal of Energy Economics and Policy, 2020)
The aim of this article is to examine the influence of energy production along with energy consumption and import on the budgetary requirement of the energy in Indonesia. The time-series data has been extracted from the database of the World Bank along with trading economics database for budgetary energy requirement from 1990 to 2015. The ARDL, Augmented Dickey-Fuller and Phillips–Perron test have been executed for hypotheses testing. The findings revealed a positive association among energy production along with energy consumption and import and budgetary requirement of the energy in Indonesia. These findings provide the guidelines to the regulation-making authorities that they should enhance their focus and development policies that improve energy production and reduce the consumption and import of the energy that enhances the economic growth and make favorable the balance of payment. This study is also provided the recommendation to the future researchers that they should improve their scope of research by adding more countries in their analysis. Keywords: Energy consumption, energy production, energy import, the budgetary energy requirement JEL Classifications: K32, O13, H6 DOI: https://doi.org/10.32479/ijeep.10587